Survey on Company and Sector Wise Share (%) of Non-Life Insurers In India: Exploring the Potential for Growth in the Indian Insurance Industry (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Indian economy hasbeen on a consistent high growth path in recent years and GDP growth in 2005-06is estimated at 8.1 percent. The industrial sector has recorded a growth of 9.4percent and agricultural sector too has bounced back showing a growth rate of2.3 percent. The service sector has grown at 9.9 percent, and the investmentclimate remained buoyant for the second consecutive year. The growth of theeconomy is also witnessed in the insurance industry. The insurance industrymirrored the overall vigorous performance of the economy and grew atapproximately 21 percent during the current year13. However, giventhe low insurance penetration and insurance density in the country whencompared to USA, Europe, Australia and many Asian countries, substantial growthcan be expected in the coming years.